1970
DOI: 10.13057/biodiv/d170149
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Fusarium as endophyte of some terrestrial orchid from Papua, Indonesia

Abstract: The aim of the study was to identify endophytic fungi associated with the roots of terrestrial orchid Phaius tankervilleae (Banks) Blume, Dendrobium lancifolium A. Rich var. papuanum and Calanthe triplicata (Willem) Ames from Papua, Indonesia. The endophytic fungi were isolated from the transversal section of the orchid roots. Identification of the endophytes was carried out based on the morphological characters. The phylogenetic analysis of nucleotide sequences generated from ITS rDNA region of the endophytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“… 52 Endophytic Fusarium promoted seed germination in Cypripedium and Platanthera . 53 As reported, fungus-plant interactions can easily shift from mutualism to parasitism depending on the plant’s physiology and environmental conditions. 54 These studies showed that it is necessary to explore the role of endophytic and nonpathogenic Fusarium strains in controlling pathogens and promoting germination and development of orchid species.…”
Section: Discussionmentioning
confidence: 95%
“… 52 Endophytic Fusarium promoted seed germination in Cypripedium and Platanthera . 53 As reported, fungus-plant interactions can easily shift from mutualism to parasitism depending on the plant’s physiology and environmental conditions. 54 These studies showed that it is necessary to explore the role of endophytic and nonpathogenic Fusarium strains in controlling pathogens and promoting germination and development of orchid species.…”
Section: Discussionmentioning
confidence: 95%
“…and Helotiales (e.g., Helotiaceae and Hyaloscyphaceae) are the main ONF associated with tropical and temperate orchids, respectively; Chaetothyriales, Hypocreales, Helotiales, and Capnodiales are also frequent in tropical epiphytic orchids (Bayman et al, 1997;Dearnaley et al, 2012;Oliveira et al, 2014;Govinda Rajulu et al, 2016;Jacquemyn et al, 2016a;Beltrán-Nambo et al, 2018;Novotná et al, 2018). In addition, Colletotrichum, Fusarium, and Trichoderma fungi are generally found in the roots of various orchids from tropical and temperate zones (Martos et al, 2012;Tao et al, 2013;Sufaati et al, 2016;Salazar-Cerezo et al, 2018;Sisti et al, 2019;Sarsaiya et al, 2020).…”
Section: Orchid Non-mycorrhizal Fungal Diversitymentioning
confidence: 99%
“…F.oxysporum fungusları genellikle orkidelerde endofit olarak bulunduğu bildirilmiştir (Ma ve ark. 2015, Sufaati 2016. Serapias vomeracea subsp.…”
Section: Doğu Ve Orta Karadeniz 'De Farklı Lokalitelerden Alınanunclassified